$\newcommand{\Cof}{\operatorname{Cof}}$ $\newcommand{\Det}{\operatorname{Det}}$ $\newcommand{\id}{\operatorname{Id}}$ $\newcommand{\tr}{\operatorname{Tr}}$

Let $A(t)$ be a smooth path in $M_d(\mathbb{R})$, $A(0)=A,\dot A(0)=B$.

By differentiation the identity $(\Cof A)^T \circ A=\Det A \cdot \id$, one gets

$$(*) \, \, \big(d(\Cof)_A(B)\big)^T \circ A + (\Cof A)^T \circ B = \tr (\Cof A)^T B) \cdot \id= \langle \Cof A , B\rangle \cdot \id$$

(The derivative of the determinant is known as Jacobi's formula).

From this, at least in the case when $A$ is invertible we can deduce that

$$ \big(d(\Cof)_A(B)\big)^T = \big(\langle \Cof A , B\rangle \cdot \id -(\Cof A)^T \circ B \big)A^{-1},$$ hence

$$ d(\Cof)_A(B) = (A^{T})^{-1}\big(\langle \Cof A , B\rangle \cdot \id - B^T \circ \Cof A \big) $$


  1. Does equation $(*)$ uniquely determine $d(\Cof)_A(B)$ even when $A$ is singular? Is there a closed formula for $d(\Cof)_A(B)$ in this case?

  2. Is there a more "direct way" to calculate $d(\Cof)_A(B)$? (without relying on Jacobi's formula)

Remark: As a corollary from $(*)$ we get $ \tr \bigg( \big(d(\Cof)_A(B)\big)^T \circ A \bigg) = (d-1) \tr (\Cof A)^T B) $

This is interesting since the cofactor essentially measures the action of the linear map $A$ on $d-1$ dimensional parallelepiped, so maybe there is a "geometric" way to see this immediately.


Let $Cof_{ij}(A)=(-1)^{i+j}\det(\Delta_{ij}(A))$, where $\Delta_{ij}(A)$ is the submatrix obtained from $A$ by deleting row $i$ and column $j$. Notice that $\Delta_{ij}(\cdot)$ is a linear transformation. Let $Adj(D)$ be the adjugate matrix of $D$.

Let $\{e_1,\ldots,e_d\}$ be the canonical basis of $\mathbb{R}^d$.

Now, $d(Cof)_A(e_me_n^t)=\lim_{h\rightarrow 0}\dfrac{Cof(A+h e_me_n^t)-Cof(A)}{h}$.

$Cof_{ij}(A+h e_me_n^t)=(-1)^{i+j}\det(\Delta_{ij}(A+h e_me_n^t))=$

$(-1)^{i+j}\det(\Delta_{ij}(A)+h \Delta_{ij}(e_me_n^t))= (-1)^{i+j}\det(\Delta_{ij}(A)+h\ uv^t)=$

By the matrix determinant lemma,

$=(-1)^{i+j}\det(\Delta_{ij}(A))+(-1)^{i+j}h\ (v^tAdj(\Delta_{ij}(A))u)$

$=(-1)^{i+j}\det(\Delta_{ij}(A))+(-1)^{i+j}h\ tr(Adj(\Delta_{ij}(A))uv^t)$

$=(-1)^{i+j}\det(\Delta_{ij}(A))+(-1)^{i+j}h\ tr(Adj(\Delta_{ij}(A))\Delta_{ij}(e_me_n^t))$

$=Cof_{ij}(A)+h\ (-1)^{i+j}\ tr(Adj(\Delta_{ij}(A))\Delta_{ij}(e_me_n^t))$.

Thus, $d(Cof)_A(e_me_n^t)=((-1)^{i+j}\ tr(Adj(\Delta_{ij}(A))\Delta_{ij}(e_me_n^t)))_{i,j}$.

Since $B=\sum_{m,n=1}^db_{m,n}e_me_n^t$ then $d(Cof)_A(B)=((-1)^{i+j}\ tr(Adj(\Delta_{ij}(A))\Delta_{ij}(B)))_{i,j}$.

  • $\begingroup$ Thanks. I do not understand some details, though: What are $u,v$ (perhaps $e_i,e_j$)? Also, do you know if my equation $(*)$ determines $d(\Cof)_A(B)$ when $A$ is singular? $\endgroup$ – Asaf Shachar Feb 13 '17 at 16:40
  • $\begingroup$ $\Delta_{ij}(e_{m}e_n^t)$ is a rank one matrix. I called it $uv^t$. Let me think about your second question. $\endgroup$ – Daniel Feb 13 '17 at 16:42
  • $\begingroup$ If $rank(A)\leq d-2$ then $Cof(A)=0$ and your formula becomes $\big(d(\Cof)_A(B)\big)^t \circ A =0$. I cannot see a way to determine $\big(d(\Cof)_A(B)\big)^t $ from the equality $XA=0$, there are infinitely many solutions. $\endgroup$ – Daniel Feb 13 '17 at 16:54
  • $\begingroup$ You are right. Thanks again! $\endgroup$ – Asaf Shachar Feb 13 '17 at 17:00
  • $\begingroup$ You are welcome. $\endgroup$ – Daniel Feb 13 '17 at 17:03

As mentioned by Daniel, when $\operatorname{rank}(A) \le d-2$, $\operatorname{Cof}(A)=0$, hence equation $(*)$ becomes

$$ \big(d(\operatorname{Cof})_A(B)\big)^T A=0$$

However, the equation $XA=0$ has infinitely many solutions, as can be seen as follows:

Look at the linear map $T:M_d \to M_d$, defined by $T(X)=X^TA$. $T$ is not surjective, since every matrix in its image has rank smaller than $d-1$. Thus, $T$ is not injective.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.